2017
DOI: 10.21873/anticanres.11453
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Conversion Surgery Following S-1 plus Cisplatin or Oxaliplatin Chemotherapy for Unresectable Gastric Cancer

Abstract: Conversion surgery after a response to CS or SOX chemotherapy may have survival benefit in selected unresectable gastric cancer patients, for both non-elderly and elderly patients responding to SOX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…A recent study concerning conversion therapy reported that the median OS and patients converted to conversion surgery did not differ significantly between S-1 plus cisplatin group and S-1 plus paclitaxel group15. Similar results were also reported by Fukuchi et al 24 that response, severe toxicity and conversion surgery were not significantly different between S-1 plus cisplatin and S-1 plus oxaliplatin. Additionally, it has been reported 21,25 that docetaxel, cisplatin and S-1 (DCS) showed a overall response rate of 73.7% to 81% and conversion surgery rate of 33% to 59.6%, which seems to be promising for conversion therapy.…”
Section: Discussionsupporting
confidence: 77%
“…A recent study concerning conversion therapy reported that the median OS and patients converted to conversion surgery did not differ significantly between S-1 plus cisplatin group and S-1 plus paclitaxel group15. Similar results were also reported by Fukuchi et al 24 that response, severe toxicity and conversion surgery were not significantly different between S-1 plus cisplatin and S-1 plus oxaliplatin. Additionally, it has been reported 21,25 that docetaxel, cisplatin and S-1 (DCS) showed a overall response rate of 73.7% to 81% and conversion surgery rate of 33% to 59.6%, which seems to be promising for conversion therapy.…”
Section: Discussionsupporting
confidence: 77%
“…ESMO Clinical Practice Guidelines also advices that gastrectomy should be actively considered in order to improve the prognosis of patients with good response to systemic chemotherapy [ 16 ]. In the research of Professor Fukuchi M et al, the median OS of patients receiving conversion therapy was 37 months, while the median OS of patients who only received chemotherapy was less than 1 year [ 17 ]. Kim SW et al studied GC patients with peritoneal metastasis and discovered that the survival time of those sufferers with complete resection was greatly improved after successful conversion therapy [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have demonstrated the prognostic impact of conversion surgery after chemotherapy for stage IV gastric cancer [ 6 8 ]. However, in most reports, conversion surgery was performed in responders after first-line chemotherapy [ 9 11 ], and there are few reports of conversion surgery in responders after second-line chemotherapy with RAM and PTX. Herein, we report a case of long-term survival of a patient with gastric cancer and liver metastases who underwent conversion surgery due to partial response to systemic second-line treatment with RAM plus PTX.…”
Section: Introductionmentioning
confidence: 99%